Characterization of denitrifying activity by the alphaproteobacterium, Sphingomonas wittichii RW1 - Cua, Lynnie S.; Stein, Lisa Y. (Frontiers in Microbiology, 2014)
Sphingomonas wittichii RW1 has no reported denitrifying activity yet encodes nitrite and nitric oxide reductases. The aims of this study were to determine conditions under which S. wittichii RW1 consumes nitrite (NO2-) and produces nitrous oxide (N2O), examine expression of putative genes for N-oxide metabolism, and determine the functionality of chromosomal (ch) and plasmid (p) encoded quinol-dependent nitric oxide reductases (NorZ). Batch cultures of wildtype (WT) and a norZch mutant of S. wittichii RW1 consumed NO2- and produced N2O during stationary phase. The norZch mutant produced N2O, although at significantly lower levels (c.a. 66-87%) relative to the WT. Rates of N2O production were 2-3 times higher in cultures initiated at low relative to atmospheric O2 per unit biomass, although rates of NO2- consumption were elevated in cultures initiated with atmospheric O2 and 1 mM NaNO2. Levels of mRNA encoding nitrite reductase (nirK), plasmid-encoded nitric oxide dioxygenase (hmpp) and plasmid-encoded nitric oxide reductase (norZp) were significantly higher in the norZch mutant over a growth curve relative to WT. The presence of NO2- further increased levels of nirK and hmpp mRNA in both the WT and norZch mutant; levels of norZp mRNA compensated for the loss of norZch expression in the norZch mutant. Together, the results suggest that S. wittichii RW1 denitrifies NO2- to N2O and expresses gene products predicted to detoxify N-oxides. So far, only S. wittichii strains within four closely related taxa have been observed to encode both nirK and norZ genes, indicating a species-specific lateral gene transfer that may be relevant to the niche preference of S. wittichii.